Aqueous Solution Blow Spinning of Seawater‐Stable Polyamidoxime Nanofibers from Water‐Soluble Precursor for Uranium Extraction from Seawater. Issue 12 (12th November 2020) - Xu, Xin; Yue, Yaru; Cai, Dong; Song, Jianan; Han, Caina; Liu, Zhongjie; Wang, Dong; Xiao, Juanxiu; Wu, Hui
Abstract: Polyamidoxime (PAO)‐based fibers are recognized as one of the most promising adsorbents for industrial‐scale extraction of uranium from seawater. The spinning of PAO is usually processed in environmentally unfriendly organic solvents, which cause serious environmental and cost concerns in industrial‐scale manufacturing. In this work, an aqueous solution blow spinning (ASBS) strategy is developed for large‐scale fabrication of seawater‐stable polyamidoxime/alginate nanofibers (PAO/Alg NFs) from water‐soluble PAO precursor solution. The as‐spun PAO/Alg NFs are ready to be used for uranium adsorption after simple immersion in calcium chloride solution for crosslinking. The 3D porous architecture, flexibility, and strength of nanofibers are well maintained as the inevitable shrinkage and degeneration accompanied by traditional "alkaline‐heat activation" post treatment are completely avoided. A high adsorption capacity of 892.77 and 8.42 mg‐U g −1 NFs is achieved in uranium spiked seawater and 8 tons of nonspiked natural seawater, respectively. Taking advantage of the simplicity, low cost, and industrially scalable features, this novel ASBS approach shows great potential for industrial‐scale production of PAO‐based nanofiber adsorbent with high capacity and good mechanical strength for uranium recovery from natural seawater and industrial wastewater. Abstract : Polyamidoxime‐based fibers are recognized as the most promising adsorbents for industrial‐scale extraction of uranium from seawater. An aqueous solution blow spinning strategy is developed for industry‐scale production of seawater‐stable polyamidoxime nanofiber adsorbent with high adsorption performance and good mechanical strength from water‐soluble polyelectrolyte precursor solution.